2007
DOI: 10.1007/s10549-007-9561-4
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer subpopulation with high risk of internal mammary lymph nodes metastasis: analysis of 2,269 Chinese breast cancer patients treated with extended radical mastectomy

Abstract: Patients with following conditions had high risk of IMNS metastasis: (1) patients with 4 or more positive ALNs. (2) patients with medial tumor and positive ALNs.(3) patients with T3 tumor and younger than 35 y. (4) patients with T2 tumor and positive ALNs.(5) patients with T2 tumor and medial tumor .The incidences of IMNS metastasis for those patients were more than 20%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
80
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(87 citation statements)
references
References 7 publications
6
80
1
Order By: Relevance
“…29 On the assumption that the IMC incidental irradiation has a therapeutic impact, an interesting note is that precisely the group that received the higher doses to the IMC comprises mastectomy patients, regardless of whether an immediate reconstruction was performed or not. These patients usually have more advanced disease, which might translate into a higher risk of relapse at the IMC, 30 and would so benefit from this approach. On the other hand, patients with multiple positive lymph nodes and undergoing conservative surgery, although with significant risk of regional recurrence, would be receiving reduced unintended radiation doses in the IMC, requiring, therefore, a regional approach with more extensive irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…29 On the assumption that the IMC incidental irradiation has a therapeutic impact, an interesting note is that precisely the group that received the higher doses to the IMC comprises mastectomy patients, regardless of whether an immediate reconstruction was performed or not. These patients usually have more advanced disease, which might translate into a higher risk of relapse at the IMC, 30 and would so benefit from this approach. On the other hand, patients with multiple positive lymph nodes and undergoing conservative surgery, although with significant risk of regional recurrence, would be receiving reduced unintended radiation doses in the IMC, requiring, therefore, a regional approach with more extensive irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…1 Surgical studies have shown that the incidence of metastatic involvement of the internal mammary nodes varies between 4% and 9% in patients with axillary node-negative breast cancer and between 16% and 65% in patients with axillary node-positive breast cancer. [2][3][4] As a consequence, surgical dissection of the internal mammary nodes was attempted but abandoned in the 1970s, since no improvement in survival was observed. 4,5 Elective irradiation of the regional nodes remained widely used until the late 1980s, when it became less popular on the basis of an overview of older trials that showed no survival benefit, despite improvement in control of locoregional disease.…”
mentioning
confidence: 99%
“…In which, breast cancer drainage to internal mammary node (IMN) happens in as many as 30% of patients [21,22] . Most of IMN metastases have concomitant axillary metastases, but 8%-10% patients with breast cancer may have IMN metastases only [23] .…”
Section: Fdg Pet/ct For Internal Mammary Lymph Nodesmentioning
confidence: 99%